Epistemological Foundations of Educational Development: Synthesizing Knowledge Construction and Pedagogical Transformation in Modern Education - Fahrizal Nover; Ahmad Syukri; Badarussyamsi (Darul Ilmi Bina Insan Foundation, 2024)
Epistemology serves as a foundational philosophical lens that defines how knowledge is constructed, validated, and integrated within educational frameworks. While traditional educational models often emphasize passive knowledge transmission, modern educational challenges require an epistemological paradigm shift toward active knowledge creation. This study explores the structural relationship between epistemological philosophy and educational development, focusing on the operational impact of knowledge construction on pedagogical methodologies and curriculum design. Utilizing a qualitative-descriptive library research approach, classical and contemporary epistemological theories ranging from rationalism and empiricism to constructivism and social epistemology were systematically synthesized and applied to educational practices. The findings reveal three core contributions of epistemology to educational transformation: (1) pedagogical shift, moving from passive instruction to critical, inquiry-based, and dialogical learning where students actively construct meaning; (2) adaptive curriculum design, providing the analytical framework necessary to filter abundant information, combat misinformation, and integrate 21st-century skills; and (3) reconciling tradition and innovation, enabling frameworks such as Islamic education to integrate classical intellectual traditions with modern scientific inquiries. In conclusion, epistemological reflection is not merely a theoretical exercise but an essential driver for developing critical, adaptive, and ethically grounded educational systems